2017
DOI: 10.1186/s13059-016-1136-4
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific analysis of cell fusion-mediated pluripotent reprograming reveals distinct and predictive susceptibilities of human X-linked genes to reactivation

Abstract: BackgroundInactivation of one X chromosome is established early in female mammalian development and can be reversed in vivo and in vitro when pluripotency factors are re-expressed. The extent of reactivation along the inactive X chromosome (Xi) and the determinants of locus susceptibility are, however, poorly understood. Here we use cell fusion-mediated pluripotent reprograming to study human Xi reactivation and allele-specific single nucleotide polymorphisms (SNPs) to identify reactivated loci.ResultsWe show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…In addition, a minority of heterokaryon and hybrid nuclei (7% at day 3 vs. 1% at day 0; unpublished data) have two diffused XIST clouds suggesting that cell fusionmediated reprogramming might be able to recapitulate some features of the in vivo epiblast cells. Consistently with this hypothesis, genome-wide expression analysis upon cell fusion-mediated reprogramming showed the reactivation of pluripotency genes associated with both primed and naïve human pluripotent cells [129] . In the future, single cell studies might indeed be used to segregate different human pluripotent states and help us refine culture conditions for naïve pluripotency.…”
Section: Reactivation By Interspecies Cell Fusionmediated Reprograsupporting
confidence: 64%
See 3 more Smart Citations
“…In addition, a minority of heterokaryon and hybrid nuclei (7% at day 3 vs. 1% at day 0; unpublished data) have two diffused XIST clouds suggesting that cell fusionmediated reprogramming might be able to recapitulate some features of the in vivo epiblast cells. Consistently with this hypothesis, genome-wide expression analysis upon cell fusion-mediated reprogramming showed the reactivation of pluripotency genes associated with both primed and naïve human pluripotent cells [129] . In the future, single cell studies might indeed be used to segregate different human pluripotent states and help us refine culture conditions for naïve pluripotency.…”
Section: Reactivation By Interspecies Cell Fusionmediated Reprograsupporting
confidence: 64%
“…To investigate the extent of Xi gene reactivation along the entire X chromosome, we derived human fibroblast clones with reciprocal Xi chromosomes (e.g. Xa 1 Xi 2 and Xi 1 Xa 2 ) and performed allele-specific RNA-seq analysis of these clones before and after reprogramming [129] . This analysis showed that cell fusion-mediated reprogramming induces partial human Xi reactivation with 10% of the sampled genes being consistently reactivated at different times after fusion and in different clones.…”
Section: Reactivation By Interspecies Cell Fusionmediated Reprogramentioning
confidence: 99%
See 2 more Smart Citations
“…Screening for chromatin modifiers that promote human Xi reactivation. The extent of expression of Xi genes in a representative clone before (hF) and after cell fusion-mediated reprogramming (hF Â mESC) reveals that some genes (highlighted in green) are susceptible to reactivation following reprogramming (for details see [71]). As pre-treatment of cells with drugs that reduced DNA methylation (þ5-aza-deoxyC) revealed a selective reactivation of additional 'Xi' genes (red dots), we propose to screen for candidate modifiers (þ agent Z) that restrict the expression of specific human X-linked genes.…”
Section: Human X-chromosome Reactivation Upon Cell Fusion-mediated Rementioning
confidence: 99%